2017
DOI: 10.1007/s10826-017-0901-7
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Courses, Training, and Interventions for Adoptive Parents

Abstract: Adoption requires thorough preparations prior to the arrival of the child and support post-adoption among parents, to promote a positive parent-child relationship and healthy family functioning. The purpose of our study was, therefore, to systematically review the literature on pre-and post-adoption interventions for caregivers, and determine the possibility for conducting a meta-analysis. We searched 12 electronic databases and identified 7 574 references that were considered for inclusion by two independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
1
11
0
3
Order By: Relevance
“…All of the included studies were found to have a high risk of bias. This echoes findings in previous literature (Drozd et al, 2017; Kerr & Cossar, 2014). Due to the lack of randomisation and control groups, the majority of included studies were rated at high risk of selection bias.…”
Section: Discussionsupporting
confidence: 92%
“…All of the included studies were found to have a high risk of bias. This echoes findings in previous literature (Drozd et al, 2017; Kerr & Cossar, 2014). Due to the lack of randomisation and control groups, the majority of included studies were rated at high risk of selection bias.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, no meta-analyses regarding parenting interventions for adoptive families have been conducted. However, a systematic review by Drozd, Bergsund, Hammerstrom, Hansen, and Jacobsen (2018) included 21 studies with a pre-/posttest design with at least one control group that examined parent outcomes in adoptive families. Some studies found improvements of interpersonal functioning and parenting, but the majority did not.…”
Section: Previous Meta-analytic Studiesmentioning
confidence: 99%
“…Among the distal variables, the child's age at adoption and length of institutionalization have been extensively explored with mixed outcomes (Niemann & Weiss, 2012;van den Dries, Juffer, van IJzendoorn, & Bakermans-Kranenburg, 2009), and effects ranging from moderate to trivial (see, e.g., Niemann & Weiss, 2012;O'Connor, Rutter, & English and Romanian Adoptees Study Team, 2000;van den Dries et al, 2009). Considering more proximal variables, robust evidence supports the finding that parental sensitivity in caregiving (commonly named positive parenting), is among the main factors affecting children's socio-emotional enhancement (Barone, Barone, Dellagiulia, & Lionetti, 2018;Drozd, Bergsund, Hammerstrøm, Hansen, & Jacobsen, 2018;Juffer, Bakermans-Kranenburg, & van IJzendoorn, 2005). Interestingly, the evidence that children's positive emotional and behavioral development is fostered by maternal sensitivity has been extensively supported by intervention studies aimed at improving maternal sensitivity and involving children biologically related to their parents.…”
Section: What Counts For Children's Recovery?mentioning
confidence: 84%